2011
DOI: 10.1162/jocn.2011.21630
|View full text |Cite
|
Sign up to set email alerts
|

The Late Positive Potential Predicts Subsequent Interference with Target Processing

Abstract: The current study investigated the association between neural engagement with task-irrelevant images and subsequent interference with target processing using the Emotional Interrupt paradigm [Mitchell, D., Richell, R., Leonard, A., & Blair, R. Emotion at the expense of cognition: Psychopathic individuals outperform controls on an operant response task. Journal of Abnormal Psychology, 115, 559, 2006]. Consistent with previous studies, PCA-derived factors corresponding to the early posterior negativity, P300, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
172
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(214 citation statements)
references
References 83 publications
30
172
7
Order By: Relevance
“…In several previous studies, the emotional modulation of the LPP and the behavioral interference were used, to some extent, interchangeably to examine the effects of emotion on attention (De Cesarei & Codispoti, 2008;Erthal et al, 2005;Ihssen, et al, 2007;MacNamara & Hajack, 2009;Padmala & Pessoa, 2014;Schupp et., al., 2006), and it has also been suggested that these two indexes are correlated (Weinberg & Hajcak, 2011). The present study indicates that, although the LPP and RTs are both modulated by motivational significance (emotional arousal) during the viewing of novel pictures, they are differentially modulated by stimulus repetition, suggesting that they do not reflect the same process.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…In several previous studies, the emotional modulation of the LPP and the behavioral interference were used, to some extent, interchangeably to examine the effects of emotion on attention (De Cesarei & Codispoti, 2008;Erthal et al, 2005;Ihssen, et al, 2007;MacNamara & Hajack, 2009;Padmala & Pessoa, 2014;Schupp et., al., 2006), and it has also been suggested that these two indexes are correlated (Weinberg & Hajcak, 2011). The present study indicates that, although the LPP and RTs are both modulated by motivational significance (emotional arousal) during the viewing of novel pictures, they are differentially modulated by stimulus repetition, suggesting that they do not reflect the same process.…”
Section: Discussionmentioning
confidence: 45%
“…Although RTs are often used to index attention to emotional stimuli (Calvo et al, 2015;Ferrari, Bruno, Chattat, & Codispoti, 2016;Hartikainen et al, 2000;Padmala & Pessoa, 2014;Weinberg & Hajcak, 2011), they are executed after a sequence of processing stages following the actual attention allocation to the stimulus, and therefore several factors might affect behavioral interference. On the other hand, the LPP is a much more temporally proximal measure of the evaluative processes involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LPP is larger for negative than for neutral pictures and also appears to be related to interference associated with irrelevant negative distractors (Weinberg & Hajcak, 2011). Most previous investigators did not comment on whether they also observed a posterior positivity following negative pictures that overlaps in time with the P3b, but it could have been overlooked because of this overlap.…”
Section: Discussionmentioning
confidence: 95%
“…Previous work in this area has shown that emotional stimuli will prime subsequent responses in a different sensory modality since stimuli in the same sensory modality are competing for limited processing resources (reviewed in Schupp et al, 2006). For example, cross modal studies show that emotional stimuli facilitate lexical decisions (Kissler and Koessler, 2011; but see Ihssen et al, 2007), enhance free recall (Herbert and Kissler, 2010), reduce response times (Scott et al, 2009;De Houwer et al, 2002;Jiang et al, 2007), improve identification of visual targets (Brosch et al, 2007(Brosch et al, , 2008Zeelenberg and Bocanegra, 2010; but see Weinberg and Hajcak, 2011), potentiate startle responses (Herbert and Kissler, 2010;reviewed in Lang et al, 1997b), augment the P1 ERP component during visual target detection (Brosch et al, 2009), and enhance touch sensation (Poliakoff et al, 2007). The motivational priming hypothesis expounded by Lang et al (1997b) particularly posits that priming will occur when there is a link or association with the emotional activation network.…”
Section: Introductionmentioning
confidence: 99%